Cognitive deficits associated with a high‐fat diet and insulin resistance are potentiated by overexpression of ecto‐nucleotide pyrophosphatase phosphodiesterase‐1. Issue 64 (31st March 2017) - Kasper, J.M.; Milton, A.J.; Smith, A.E.; Laezza, F.; Taglialatela, G.; Hommel, J.D.; Abate, N.
Abstract: There is growing evidence that over consumption of high‐fat foods and insulin resistance may alter hippocampal‐dependent cognitive function. To study the individual contributions of diet and peripheral insulin resistance to learning and memory, we used a transgenic mouse line that overexpresses ecto‐nucleotide pyrophosphatase phosphodiesterase‐1 in adipocytes, which inhibits the insulin receptor. Here, we demonstrate that a model of peripheral insulin resistance exacerbates high‐fat diet induced deficits in performance on the Morris Water Maze task. This finding was then reviewed in the context of the greater literature to explore potential mechanisms including triglyceride storage, adiponectin, lipid composition, insulin signaling, oxidative stress, and hippocampal signaling. Together, these findings further our understanding of the complex relationship among peripheral insulin resistance, diet and memory.